Aspek Aspek Pemaknaan Kriminologi pada Film Film Mencuri Raden Saleh - Soelaiman, Mutiara Adinia; Rahmat Wisudawanto (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Films have a huge impact in changing the perception of the audience. The film "Stealing Raden Saleh" presents a storyline that contains criminology scenes. Sometimes, perpetrators of crimes are not aware of their actions, because there are many factors that support them. This research aims to reveal the meaning of criminology in films using Roland Barthes' Semiotic Analysis. The film features various crime scenes, including theft, forgery of paintings, threats of violence, and fights. A qualitative approach was used in this research, with the aim of determining, understanding, explaining and gaining an in-depth understanding of the signs manifested in images and dialogue to describe the forms of crime represented in this film. The analytical method applied is qualitative based on Roland Barthes' semiotic model. By using the theory of denotation, connotation and myth, this research found that the most dominant criminological category from the data was the role of peers.